Steel sheet and producing method thereof
Patent Information
- Application Number
- JP2024122642
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-23
- Filing Date
- 2024-07-29
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-07-29
AI Technical Summary
【0019】 本発明によれば、別途の矯正加工の工程を経ずともタンクの製造等に使用することができ、低温での靭性および耐アンモニア応力腐食割れ性に優れた、低温かつ液化アンモニアによる腐食雰囲気の環境で供されるタンクに用いて好適な鋼板を、その製造方法と共に提供することができる。
Smart Images

Figure 2025031576000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a steel plate having excellent low-temperature toughness and ammonia stress corrosion cracking resistance and is used for tanks for carrying liquefied petroleum gas (hereinafter referred to as LPG) or liquefied ammonia, and a manufacturing method thereof. [Background technology]
[0002] Toward the realization of a low-carbon society, ammonia, which does not emit carbon dioxide when burned, is attracting attention as a new energy source. Hydrogen is also a candidate for clean energy because it does not emit carbon dioxide when burned, and ammonia is also seen as a promising form for transporting such hydrogen stably. Here, it is assumed that international transportation of liquefied ammonia will mainly be by ship. In addition, since there will be demand for fossil fuels as an energy source in the medium term, it is expected that there will be a shift in cargo between liquefied ammonia and other cargoes, such as LPG, liquefied butane, dimethyl ether, and butene, or mixed transport.
[0003] Since LPG and ammonia are loaded in tanks as liquefied gas at low temperatures, the base materials used in the tanks are required to have excellent low-temperature toughness. In addition, liquefied ammonia is known to cause stress corrosion cracking of steel materials. Therefore, from the perspective of ensuring the safety of tanks, measures must be taken to prevent stress corrosion cracking caused by liquefied ammonia.To prevent stress corrosion cracking caused by liquefied ammonia, the IGC Code (International Code for the Construction and Equipment of Ships Carrying Liquefied Gases in Bulk), which is an international regulation for ships and equipment that transport liquefied gases, specifies measures such as setting the yield point (hereinafter referred to as YS) of carbon manganese steel for tanks at 440 MPa or less and carrying out treatment to remove welding residual stress during the tank manufacturing process.
[0004] Furthermore, tanks are becoming larger to improve transport efficiency, and the steel materials used in these tanks are required to have high tensile strength (hereinafter referred to as TS). Specifically, steel materials for LPG and liquefied ammonia tanks are required to have toughness with a ductile-brittle fracture transition temperature vTrs of -55°C or less, and mechanical properties in the ranges of YS of 325 to 440 MPa and TS of 440 to 560 MPa. Furthermore, there is also a demand for steel materials with equivalent toughness, YS of 355 to 440 MPa, and TS of 490 to 610 MPa.
[0005] Such technologies that provide the low-temperature toughness required for liquefied gas tanks and satisfy the restrictions on YS and the demand for high TS are described in Patent Documents 1 to 3. That is, in the technique disclosed in Patent Document 1, the morphology of ferrite is controlled by hot rolling and accelerated cooling to suppress the yield ratio of the base material.
[0006] Furthermore, in the technology disclosed in Patent Document 2, a low yield ratio of the base material is achieved by controlling the grain size distribution of ferrite through hot rolling and multiple accelerated cooling processes.
[0007] In addition, Patent Document 3 discloses a technique for distributing a hard phase by hot rolling and accelerated cooling, thereby creating a difference in hardness with ferrite, thereby reducing the yield ratio. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2006-89830 A [Patent Document 2] JP 2019-214752 A [Patent Document 3] JP 2010-90406 A Summary of the Invention [Problem to be solved by the invention]
[0009] However, the methods described in Patent Documents 1 and 2 require accelerated cooling after hot rolling. In particular, when the plate thickness is 15 mm or less, there is a problem that thermal deformation occurs due to accelerated cooling, deteriorating the flatness of the steel plate.
[0010] Furthermore, the technology disclosed in Patent Document 3 makes it possible to manufacture low-yield-ratio steel by air cooling, but there is concern about a decrease in toughness due to the presence of hard phases. In addition, the addition of two or more of Cu, Ni, Cr, and Mo is required, and there is room for improvement in manufacturing costs.
[0011] In any case, in the steel plates to which the above-mentioned conventional techniques are applied, accelerated cooling is required in the manufacturing process, and therefore the flatness of the steel plates to which such techniques are applied is deteriorated, making it extremely difficult to use such steel plates for the manufacture of tanks as described above as steel plates that do not require a separate straightening process. Moreover, adding such a straightening process not only increases manufacturing time and costs, but also leads to an excessive increase in YS due to work hardening during straightening, which may make it impossible to manufacture the above-mentioned tank.
[0012] The present invention aims to solve the above-mentioned various problems and to provide a steel plate for use in tanks of liquefied gas carriers or for storing liquefied gas, which not only ensures ammonia stress corrosion cracking resistance by satisfying the YS regulation, but also has excellent low-temperature toughness without the need for a separate straightening process, and a manufacturing method thereof. [Means for solving the problem]
[0013] In order to achieve the above object, the inventors have investigated strength control factors for improving TS within a range in which YS does not exceed 440 MPa while maintaining the low temperature toughness of the steel plate. As a result, they have found that it is effective to contain elements such as C, Si, Mn, Ti, etc. in predetermined amounts, control bainite at a position 0.5 mm from the surface of the steel plate to a predetermined volume fraction, set the volume fraction of ferrite at a position 1 / 4 of the plate thickness to 50% or more and 90% or less, and configure the grain size distribution of ferrite to a predetermined configuration. By satisfying the requirements of this configuration, the fine ferrite ensures toughness at low temperatures, while the coarse ferrite controls the onset of yielding, thereby improving TS while satisfying the requirements stipulated in the IGC Code.Furthermore, it was found that the excellent flatness of the resulting steel sheet makes it possible to reduce manufacturing costs.
[0014] The present invention was completed based on these findings and through further investigation. That is, the gist of the present invention is as follows. 1. By mass%, C: 0.06% or more and 0.13% or less, Si: 0.10% or more and 0.30% or less, Mn: 0.50% or more and 2.00% or less, P: 0.030% or less, S: 0.0030% or less, Al: 0.010% or more and 0.060% or less, Nb: 0.005% or more and 0.030% or less, Ti: 0.004% or more and 0.030% or less, Ca: 0.0005% or more and 0.0030% or less, N: 0.0010% or more and 0.0070% or less, and O: 0.0040% or less, The carbon equivalent (Ceq) represented by the following formula (1) is 0.31 or more and 0.40 or less, with the balance being Fe and unavoidable impurities, The volume fraction of bainite at a position 0.5 mm from the surface of the steel plate is 20% or less, Furthermore, at the 1 / 4 position of the plate thickness, The volume fraction of ferrite is 50% or more and 90% or less, And, the total number of ferrite particles with a circle equivalent diameter of 2 μm or more, The percentage of ferrite particles with a circle equivalent diameter of less than 10 μm is 80% or more and 95% or less, The number ratio of ferrite particles having a circle equivalent diameter of 10 to 20 μm is 4% or more and 20% or less, Equivalent circle diameter: The number of ferrite particles exceeding 20 μm is 1% or less. steel plate. Ceq=C+Mn / 6+(Cu+Ni) / 15+(V+Mo+Cr) / 5 (1) Here, the element symbols in the above formula (1) represent the content (mass%) of each element in the steel, and when no element is contained, the value is set to 0.
[0015] 2. The steel plate according to 1 above, containing, in addition to the above-mentioned chemical composition, one or more elements selected from, by mass%, Cu: 2.00% or less, Ni: 2.00% or less, Cr: 1.00% or less, Mo: 1.00% or less, V: 1.00% or less, W: 1.00% or less, and Co: 1.00% or less.
[0016] 3. The steel plate according to 1 or 2 above, wherein when a 2 m long piece is placed on the surface of the steel plate along the rolling direction, the maximum gap between the surface of the steel plate and the long piece is 14 mm or less.
[0017] 4. In mass%, C: 0.06% or more and 0.13% or less, Si: 0.10% or more and 0.30% or less, Mn: 0.50% or more and 2.00% or less, P: 0.030% or less, S: 0.0030% or less, Al: 0.010% or more and 0.060% or less, Nb: 0.005% or more and 0.030% or less, Ti: 0.004% or more and 0.030% or less, Ca: 0.0005% or more and 0.0030% or less, N: 0.0010% or more and 0.0070% or less, and O: 0.0040% or less, A steel material having a composition in which the carbon equivalent (Ceq) represented by the following formula (1) is 0.31 or more and 0.40 or less, with the balance being Fe and unavoidable impurities, When hot rolling, After heating to a temperature of 950℃ or higher and 1250℃ or lower, The hot rolling start temperature is set to Ar3 transformation point + 150℃ or higher. The cumulative rolling reduction in the non-recrystallization temperature region is 25% or more and 75% or less, The difference between the maximum temperature and the minimum temperature in the width direction of the steel sheet during rolling in the non-recrystallization temperature region is set to 50° C. or less, Hot rolling is performed so that the hot rolling finish temperature (FT) satisfies the relationship of the following formula (2), After the hot rolling is completed, the steel sheet is cooled to room temperature at a cooling rate of 5.0°C / s or less at a position 0.5 mm from the surface. Manufacturing method of steel plate. Ceq=C+Mn / 6+(Cu+Ni) / 15+(V+Mo+Cr) / 5 (1) Here, the element symbols in formula (1) represent the content (mass%) of each element in the steel, and 0 is used when the element is not contained. Ar3+1250×Ceq-450 <FT (2) Here, FT represents the hot rolling finish temperature (°C), and Ar3 represents the temperature (°C) of the Ar3 transformation point during the cooling process.
[0018] 5. A method for producing a steel sheet as described in 4 above, which contains, in addition to the above-mentioned chemical composition, one or more selected from, by mass%, Cu: 2.00% or less, Ni: 2.00% or less, Cr: 1.00% or less, Mo: 1.00% or less, V: 1.00% or less, W: 1.00% or less, and Co: 1.00% or less. Effect of the Invention
[0019] According to the present invention, it is possible to provide a steel plate which can be used for the manufacture of tanks without a separate straightening process, has excellent toughness and resistance to ammonia stress corrosion cracking at low temperatures, and is suitable for use in tanks used in low-temperature environments in corrosive atmospheres due to liquefied ammonia, together with a manufacturing method thereof. [Brief description of the drawings]
[0020] [Figure 1] FIG. 2 is a schematic diagram showing how to measure flatness according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] The steel material and steel plate of the present invention will be specifically described below. In the present invention, it is important that the steel plate and the steel material used for the production thereof have the above-mentioned specific composition. Therefore, the reason for limiting the composition of the steel material and steel plate in the present invention to the above-mentioned composition will be described first. Note that "%" regarding the composition means "mass %" unless otherwise specified.
[0022] [Component composition] C: 0.06% or more and 0.13% or less C is an element that acts to increase the hardenability of steel, and is one of the important elements that must be contained to achieve high tensile strength (TS). In order to obtain this effect, the C content is set to 0.06% or more. Furthermore, from the viewpoint of reducing the content of other alloy elements and manufacturing at lower cost, the C content is preferably set to 0.08% or more. On the other hand, from the viewpoint of suppressing deterioration of toughness and weldability, a small C content is preferable, but in the present invention, up to 0.13% is allowed. The C content is preferably set to 0.11% or less.
[0023] Si: 0.10% or more and 0.30% or less Si is an element that acts as a deoxidizer, and in order to obtain this effect, the Si content is set to 0.10% or more. On the other hand, Si is an element that reduces toughness and weldability, but in the present invention, the Si content is allowed to be up to 0.30%. Note that if the Si content exceeds 0.20%, island martensite may be generated in the HAZ formed during welding with a large heat input, which may deteriorate the toughness, so the Si content is preferably set to 0.20% or less.
[0024] Mn: 0.50% or more and 2.00% or less Mn is an element that acts to increase the hardenability of steel, and is one of the important elements that must be contained to satisfy high tensile strength (TS). In order to obtain the above effect, the Mn content is set to 0.50% or more. Furthermore, from the viewpoint of reducing the content of other alloy elements and manufacturing at a lower cost, the Mn content is preferably set to 0.90% or more, and more preferably set to 1.20% or more. On the other hand, if the Mn content exceeds 2.00%, in addition to the deterioration of toughness and weldability, the alloy cost becomes excessively high. Therefore, the Mn content is set to 2.00% or less. Furthermore, from the viewpoint of suppressing the deterioration of toughness and weldability, the Mn content is preferably set to 1.80% or less, and more preferably set to 1.60% or less.
[0025] P:0.030% or less P has adverse effects such as reducing toughness and weldability by segregating at grain boundaries. Therefore, it is desirable to make the P content as low as possible, but 0.030% or less is acceptable. The lower limit of the P content is not particularly limited and may be 0%, but since P is usually an element that is inevitably contained in steel as an impurity, it may be more than 0% industrially. In addition, since excessive reduction of P leads to an increase in refining costs, it is preferable that the P content is 0.0005% or more.
[0026] S: 0.0030% or less S is an element that exists in steel as sulfide-based inclusions such as MnS, and acts as a starting point for brittle cracks, reducing the toughness of the base material. Therefore, it is desirable to reduce the S content as much as possible, but 0.0030% or less is acceptable. The lower limit of the S content is not particularly limited and may be 0%. Since S is usually an element that is inevitably contained in steel as an impurity, it may be more than 0% industrially. In addition, excessive reduction of S leads to an increase in refining costs, so from the viewpoint of cost, it is preferable to set the S content to 0.0005% or more.
[0027] Al: 0.010% or more and 0.060% or less Al acts as a deoxidizer and is an element that has the effect of refining crystal grains and improving the toughness of the base material. In order to obtain these effects, the Al content is set to 0.010% or more. On the other hand, if the Al content exceeds 0.060%, oxide-based inclusions increase, and the cleanliness and toughness of the base material decrease. The decrease in cleanliness leads to deterioration of the surface properties due to an increase in surface defects and a decrease in bending workability. Therefore, the Al content is set to 0.060% or less. It is preferable that the Al content is set to 0.050% or less.
[0028] Nb: 0.005% or more and 0.030% or less Nb is an element that reduces the prior austenite grain size by precipitating as carbonitride, contributes to the refinement of the structure by hot rolling, and improves the YS and TS of the base material. In order to effectively obtain these effects in the manufacturing process of the present invention, the Nb content needs to be 0.005% or more. The Nb content is preferably 0.010% or more. On the other hand, if the Nb content exceeds 0.030%, the YS exceeds 440 MPa due to excessive refinement of the structure when the manufacturing process of the present invention is used. Therefore, the Nb content is set to 0.030% or less.
[0029] Ti: 0.004% or more and 0.030% or less Ti is an element that has a strong tendency to form nitrides, and precipitates as TiN during solidification, suppresses the coarsening of austenite during the heating process of the steel material, and contributes to high toughness of the base material by becoming a ferrite transformation nucleus. In order to obtain this effect, the Ti content is set to 0.004% or more. Furthermore, if the Ti content is 0.012% or more, a large amount of TiN is precipitated, and the effect of suppressing the coarsening of austenite is significantly exhibited, so the Ti content is preferably set to 0.012% or more. On the other hand, if the Ti content exceeds 0.030%, the particles of TiN become coarse, the effect of suppressing the coarsening of austenite cannot be obtained, and the toughness decreases. Therefore, the Ti content is set to 0.030% or less. Furthermore, the Ti content is preferably set to 0.020% or less.
[0030] Ca: 0.0005% or more and 0.0030% or less Ca is an element that combines with S and has the effect of suppressing the formation of MnS and the like that elongates in the rolling direction. Therefore, by containing a predetermined amount of Ca, the morphology of the sulfide-based inclusions can be controlled to be spherical, and the toughness of the base material can be improved. Furthermore, if the Ca content is less than 0.0005%, the toughness of the base material becomes inferior. Therefore, the Ca content must be 0.0005% or more. Furthermore, the Ca content is preferably 0.0015% or more. On the other hand, if the Ca content exceeds 0.0030%, the cleanliness of the steel decreases. The decrease in cleanliness leads to deterioration of the surface properties due to an increase in surface defects and a decrease in bending workability. Therefore, the Ca content is set to 0.0030% or less. The Ca content is preferably 0.0025% or less.
[0031] N: 0.0010% or more and 0.0070% or less N combines with Ti to precipitate as TiN, contributing to refinement of the microstructure and improving the YS and toughness of the base material. In order to obtain such an effect, the N content is set to 0.0010% or more. The N content is preferably 0.0030% or more, more preferably 0.0050% or more. On the other hand, if the N content exceeds 0.0070%, the amount of solid-solubilized N increases, leading to a decrease in the base material toughness. Also, if the N content exceeds 0.0070%, the weldability decreases. Therefore, from the viewpoint of suppressing the decrease in the base material toughness and weldability, the N content is set to 0.0070% or less. The N content is preferably set to 0.0060% or less.
[0032] O: 0.0040% or less Since O is an element that forms oxides, becomes the initiation point of brittle cracks, and reduces the toughness of the base material, the O content is limited to 0.0040% or less. In addition, the O content is preferably 0.0030% or less. On the other hand, the lower limit of the O content is not particularly limited and may be 0%, but since O is usually an element that is inevitably contained in steel as an impurity, it may be more than 0% industrially. In other words, since excessive reduction of O leads to an increase in refining costs, from the viewpoint of cost, it is preferable that the O content is 0.0020% or more.
[0033] Carbon equivalent Ceq: 0.31 to 0.40 In the present invention, in order to satisfy the predetermined mechanical properties of the base material, it is essential that the carbon equivalent (Ceq) defined by the formula (1), Ceq=C+Mn / 6+(Cu+Ni) / 15+(Cr+Mo+V) / 5, be 0.31 or more and 0.40 or less. When the Nb content is in the range of 0.005% to 0.030%, if the carbon equivalent is less than 0.31, the hard phase is insufficient and the specified TS cannot be achieved. On the other hand, when the Nb content is in the range of 0.005% to 0.030%, if the carbon equivalent exceeds 0.40, the hard phase is excessively generated, TS and YS become excessively high, and the occurrence of stress corrosion cracking due to ammonia cannot be prevented.
[0034] The basic composition of the present invention includes the above components, with the balance being Fe and unavoidable impurities. This basic composition may further contain at least one selected from the group consisting of Cu: 2.00% or less, Ni: 2.00% or less, Cr: 1.00% or less, Mo: 1.00% or less, V: 1.00% or less, W: 1.00% or less, and Co: 1.00% or less, for the purpose of improving strength characteristics or toughness. The lower limit of each of the above groups is about 0.02% in order to obtain the effect of each element. Although there is no problem with the content below the lower limit, such elements are treated as unavoidable impurities.
[0035] Cu:2.00% or less Cu is an element that has the effect of increasing the hardenability of steel and improving the strength of the steel sheet, and can be contained as desired. On the other hand, if the Cu content exceeds 2.00%, it leads to a deterioration in toughness and an increase in alloy cost. Therefore, when Cu is contained, the Cu content is set to 2.00% or less. The Cu content is more preferably 1.00% or less.
[0036] Ni: 2.00% or less Ni is an element that has the effect of improving the strength of the steel sheet, similar to Cu, and can be contained as desired. On the other hand, if the Ni content exceeds 2.00%, it leads to deterioration of weldability and an increase in alloy cost. Therefore, when Ni is contained, the Ni content is set to 2.00% or less. The Ni content is more preferably 1.00% or less.
[0037] Cr:1.00% or less Cr is an element that has the effect of improving the strength of the steel sheet, similar to Cu, and can be included as desired. On the other hand, if the Cr content exceeds 1.00%, it leads to deterioration of weldability and an increase in alloy cost. Therefore, if Cr is included, the Cr content is set to 1.00% or less. The Cr content is more preferably 0.50% or less.
[0038] Mo: 1.00% or less Mo, like Cu, is an element that improves the strength of the steel sheet, and can be added as desired. On the other hand, if the Mo content exceeds 1.00%, it leads to deterioration of weldability and an increase in alloy costs. Therefore, if Mo is added, the Mo content is set to 1.00% or less. The Mo content is more preferably 0.30% or less.
[0039] V: 1.00% or less V, like Cu, is an element that has the effect of improving the strength of the steel sheet, and can be contained as desired. On the other hand, if the V content exceeds 1.00%, it leads to deterioration of weldability and an increase in alloy costs. Therefore, when V is contained, the V content is set to 1.00% or less. The V content is more preferably 0.30% or less.
[0040] W: 1.00% or less W is an element that has the effect of improving the strength of the steel sheet, similar to Cu, and can be contained as desired. On the other hand, if the W content exceeds 1.00%, it leads to deterioration of weldability and an increase in alloy cost. Therefore, if W is contained, the W content is set to 1.00% or less. The W content is more preferably 0.40% or less.
[0041] Co: 1.00% or less Co is an element that has the effect of improving the strength of the steel sheet, similar to Cu, and can be optionally contained. On the other hand, if the Co content exceeds 1.00%, it leads to deterioration of weldability and an increase in alloy cost. Therefore, if Co is contained, the Co content is set to 1.00% or less. The Co content is more preferably 0.50% or less.
[0042] In addition to having the above-mentioned chemical composition, it is important that the steel plate of the present invention has a microstructure in which the volume fraction of bainite at a position 0.5 mm from the surface of the steel plate is 20% or less, the volume fraction of ferrite at a position 1 / 4 of the plate thickness is 50% to 90% and the proportion of ferrite particles with an equivalent circle diameter of less than 10 μm in the total number of ferrite particles with an equivalent circle diameter of 2 μm or more is 80% to 95%, the proportion of ferrite particles with an equivalent circle diameter of 10 to 20 μm is 4% to 20%, and the proportion of ferrite particles with an equivalent circle diameter of more than 20 μm is 1% or less. The reasons for limiting the microstructure as described above will be explained below.
[0043] [Microstructure] The microstructure of the steel sheet of the present invention will be described below. [Volume fraction of bainite at a position 0.5 mm from the steel plate surface is 20% or less] In the present invention, the volume fraction of bainite at a position 0.5 mm from the surface of the steel sheet is 20% or less. When bainite is formed, transformation strain occurs inside the steel sheet. If the volume fraction of bainite at a position 0.5 mm from the surface of the steel sheet exceeds 20%, the steel sheet will warp due to the accumulation of such transformation strain, and the flatness will deteriorate. Preferably, the volume fraction of bainite is 10% or less.
[0044] The type of the remaining structure at a position 0.5 mm from the surface of the steel sheet is not particularly limited, but may be a mixture of structures such as ferrite, pearlite, austenite, and martensite. The volume fraction of each structure in the remaining structure does not need to be particularly limited, but from the viewpoint of the flatness and toughness of the steel sheet, it is preferable that the volume fraction of ferrite or pearlite in the remaining structure is high. The volume fractions of various microstructures can be measured by the method described in the Examples below.
[0045] [At the 1 / 4 position of the plate thickness, the volume fraction of ferrite is 50% to 90%] The structure at the 1 / 4 position of the plate thickness has a ferrite volume fraction in the range of 50% to 90%. If the ferrite volume fraction exceeds 90%, the specified TS is not reached due to a lack of hard phase. On the other hand, if the ferrite volume fraction is less than 50%, the remaining structure contains more hard phases such as pearlite and martensite, so that the TS and YS exceed the specified range and the toughness of the base material decreases. Preferably, the ferrite volume fraction is 60% or more. Also, preferably, the ferrite volume fraction is 80% or less.
[0046] The type of the remaining structure at the 1 / 4 position of the plate thickness is not particularly limited, and may be a mixture of structures such as pearlite, austenite, bainite, martensite, etc. The volume fraction of each structure in the remaining structure does not need to be particularly limited, but from the viewpoint of toughness, it is preferable that the volume fraction of pearlite or bainite in the remaining structure is the second highest after ferrite.
[0047] In the present invention, the grain size distribution of ferrite grains in the total number of ferrite grains having a circle equivalent diameter of 2 μm or more at the 1 / 4 position of the sheet thickness is specified as follows. In the present invention, the grain size of ferrite refers to the equivalent circle diameter, which is the diameter of a circle having the same area as one grain of ferrite projected onto a two-dimensional plane. The equivalent circle diameter is calculated by performing image analysis processing on an image of a microstructure. In such image analysis, noise due to insufficient resolution of the image to be analyzed or lens focus deviation during shooting may be judged as grains, and calculations may be made to indicate the presence of a huge amount of minute ferrite. Therefore, in the present invention, ferrite with a size that can be visually judged as crystal, i.e., a circle equivalent diameter of 2 μm or more, is treated as grains. Therefore, unless otherwise specified in the present invention, when ferrite crystal grains are mentioned, the subject matter is ferrite crystal grains having an equivalent circle diameter of 2 μm or more.
[0048] [Circle equivalent diameter: The number of ferrite particles less than 10 μm is 80% to 95%] Since the greater the proportion of fine ferrite, the better the toughness at low temperatures, the proportion of ferrite with a circle equivalent diameter of less than 10 μm must be 80% or more in a steel sheet containing Nb in the range of 0.005% to 0.030%. On the other hand, if there is an excessive amount of fine ferrite, the soft phase ferrite is less likely to yield, and the YS exceeds the specified range. Therefore, in a steel sheet containing Nb in the range of 0.005% to 0.030%, the proportion of ferrite with a circle equivalent diameter of less than 10 μm is 95% or less. Preferably, the proportion of ferrite with a circle equivalent diameter of less than 10 μm is 85% or more. Also, preferably, the proportion of ferrite with a circle equivalent diameter of less than 10 μm is 92% or less.
[0049] [Circle equivalent diameter: The number of ferrite particles with diameters of 10 to 20 μm is 4% to 20%] Since ferrite with a circle equivalent diameter of 10 μm or more has a lower yield stress than ferrite with a circle equivalent diameter of less than 10 μm or hard phase, it becomes plastic relatively early with the action of an external force in the tensile direction. This makes it possible to control the YS of the steel sheet. In order to obtain a predetermined YS range in a steel sheet containing Nb in the range of 0.005% to 0.030%, ferrite with a circle equivalent diameter of 10 to 20 μm is required in a number ratio of 4% to 20%. When the amount of ferrite with a circle equivalent diameter of 10 to 20 μm is less than 4%, the number of ferrite grains that are prone to yielding is reduced, and the YS exceeds 440 MPa. On the other hand, ferrite with a circle equivalent diameter of 10 to 20 μm becomes the starting point of brittle cracks at low temperatures, which leads to a decrease in the toughness of the steel sheet, so the number ratio is set to 20% or less. Preferably, the number ratio of ferrite with a circle equivalent diameter of 10 to 20 μm is 8% or more. Also, preferably, the percentage of ferrite particles having an equivalent circle diameter of 10 to 20 μm is 13% or less.
[0050] [Circle equivalent diameter: The number of ferrite particles exceeding 20 μm is 1% or less] Ferrite with a circle equivalent diameter exceeding 20 μm contributes to suppressing the YS of the steel plate, but significantly reduces the low-temperature toughness of the steel plate. Therefore, in a steel plate containing Nb in the range of 0.005% to 0.030%, the number ratio is set to 1% or less. If the number ratio of ferrite with a circle equivalent diameter exceeding 20 μm is 1% or less, there is no problem with the toughness in the service environment, but the number ratio is preferably 0.4% or less. The lower limit of the number ratio of ferrite with a circle equivalent diameter exceeding 20 μm is not particularly limited and may be 0%.
[0051] In the present invention, the plate thickness is not particularly limited, but it is preferable that the plate thickness is 14 mm or less, because the plate has excellent flatness. The flatness of steel plates of such a thickness is particularly likely to deteriorate. Therefore, when the present invention is applied, even steel plates that do not undergo a separate straightening process can obtain the flatness described below, and can be advantageously used in the manufacture of tanks as described above.
[0052] Next, a method for producing a steel sheet according to the present invention will be described. A steel material having the above-mentioned composition is heated and hot-rolled to obtain a hot-rolled steel sheet, which is then cooled under the conditions described below to obtain a steel sheet. Each manufacturing condition will be described in detail below.
[0053] The method for producing the steel material is not particularly limited, but it is preferable to produce molten steel having the above-mentioned composition by a known melting method such as a converter, and to produce a steel material such as a slab of a predetermined size by a known casting method such as a continuous casting method. There is no problem in producing a steel material such as a slab of a predetermined size by an ingot casting-disassembly rolling method.
[0054] The steel material thus obtained is either directly subjected to hot rolling without cooling, or is once cooled and then heated before being subjected to hot rolling. In this hot rolling, the steel material is heated to a temperature of 950°C to 1250°C, and then rolling is started at a temperature of Ar3 transformation point +150°C or higher, the cumulative reduction in the austenite non-recrystallization temperature range is set to 25% to 75%, and the hot rolling is completed at a predetermined temperature. Next, the steel plate is cooled to room temperature at a cooling rate of 5.0°C / s or lower at a position 0.5 mm from the surface.
[0055] (a) Heating temperature of steel material: 950℃ to 1250℃ If the heating temperature of the steel material is less than 950°C, the heating temperature is too low, resulting in high deformation resistance of the steel material, which increases the load on the hot rolling machine and makes hot rolling difficult. On the other hand, if the heating temperature exceeds 1250°C, oxidation of the surface of the material becomes significant, which increases the oxidation loss of the material and reduces the yield. For these reasons, the heating temperature of the steel material is set to 950°C or higher and 1250°C or lower. The heating temperature of the steel material is preferably 1000°C or higher. The heating temperature of the steel material is preferably 1150°C or lower.
[0056] (b) Hot rolling start temperature: Ar3 transformation point + 150°C or higher After the steel material is heated to the aforementioned heating temperature, hot rolling is carried out. In this case, if the temperature at which hot rolling starts is less than the Ar3 transformation point + 150°C, it becomes difficult to set the hot rolling end temperature (described later) to the specified temperature, particularly in the case of a steel plate with a final product thickness of 14 mm or less, and the specified strength characteristics and toughness cannot be obtained. Therefore, the hot rolling start temperature is set to the Ar3 transformation point + 150°C or higher. From the viewpoint of ensuring the time for rolling in the non-recrystallized region described later, the hot rolling start temperature is preferably set to the Ar3 transformation point + 250° C. or more. The upper limit of the hot rolling start temperature usually follows the heating temperature of the steel material described above.
[0057] Here, the Ar3 transformation point (°C) can be calculated, for example, by the following formula. Ar3(℃)=910-273×C-74×Mn-57×Ni-16×Cr-9×Mo-5×Cu However, each element symbol indicates the content (mass%) of the corresponding element in the steel, and if the corresponding element is not contained, it is set to zero.
[0058] (c) Cumulative rolling reduction in the non-recrystallization temperature range: 25% to 75% In the austenite non-recrystallization temperature region (meaning in the present invention the region where the steel material is at a temperature below the Ar3 transformation point + 150°C) with the component composition of the present invention, if the cumulative rolling reduction is less than 25%, the austenite is not sufficiently worked during hot rolling. If the austenite is not sufficiently worked in this way, the number of ferrite nucleation sites will be reduced in the cooling process described below, and the proportion of ferrite particles with a circle equivalent diameter exceeding 20 μm will exceed 1%, or the proportion of ferrite particles with a circle equivalent diameter less than 10 μm will be less than 80%. In such cases, the toughness of the base material will decrease, and the YS will not reach the specified value.
[0059] On the other hand, when the cumulative rolling reduction in the non-recrystallization temperature region exceeds 75% with the composition of the present invention, the percentage of fine ferrite particles with a circle equivalent diameter of less than 10 μm exceeds 95%, or the percentage of ferrite particles with a circle equivalent diameter of 10 to 20 μm becomes less than 4%. In such cases, the YS of the steel sheet exceeds 440 MPa. Therefore, the cumulative rolling reduction in the non-recrystallization temperature region is limited to 25% or more and 75% or less. From the viewpoint of improving toughness at low temperatures, the cumulative rolling reduction is preferably set to 40% or more, and more preferably set to 50% or more.
[0060] (d) The difference between the maximum and minimum temperatures in the width direction of the steel sheet during rolling in the non-recrystallization temperature region: 50°C or less During hot rolling, the temperature of a steel plate drops when it comes into contact with rolls or descaling water and when it waits between rolling passes. In particular, the temperature is more likely to drop at the width ends of the steel plate, but less likely to drop at the width center. It was found that when there is a temperature distribution in the width direction of a steel plate, the resistance to hot rolling differs in the width direction, resulting in a difference in the degree of deformation caused by rolling. If the difference between the maximum and minimum temperatures in the width direction of the steel sheet exceeds 50°C, the steel sheet will warp during hot rolling, and the flatness of the steel sheet after hot rolling will exceed a predetermined range. Therefore, in the present invention, the difference between the maximum and minimum temperatures in the width direction of the steel sheet during rolling in the non-recrystallization temperature region must be 50°C or less. Preferably, the difference between the maximum and minimum temperatures in the width direction of the steel sheet during rolling in the non-recrystallization temperature region is 30°C or less. The temperature of the steel sheet during hot rolling refers to the temperature of the steel sheet surface measured by a radiation thermometer. The width-direction distribution of the steel sheet surface temperature is measured immediately before the steel sheet is transported to the rolling rolls, and the highest point of the temperature profile is the maximum temperature, and the lowest point is the minimum temperature. The temperature measurement position in the longitudinal direction of the steel sheet is near the longitudinal center where the temperature is stable.
[0061] (e) Hot rolling finish temperature (FT): (Ar3+1250×Ceq-450)℃ or more In order to obtain a steel sheet structure having a predetermined ferrite grain size distribution (predetermined ferrite grain size distribution) according to the present invention, it is necessary to strictly control the degree of deformation introduced into austenite. The inventors have found the above hot rolling end temperature condition as a result of their investigations. That is, in the case of the composition of the present invention, if the hot rolling end temperature is (Ar3+1250×Ceq-450)°C or lower, the number ratio of fine ferrite particles with a circle equivalent diameter of less than 10 μm exceeds 95%, or the number ratio of ferrite particles with a circle equivalent diameter of 10 to 20 μm becomes less than 4%. As a result, the toughness of the base material decreases, and the base material YS exceeds the specified range. Therefore, in the present invention, it is necessary that the hot rolling finish temperature (FT), together with the Ar3 transformation point and the carbon equivalent Ceq, satisfy the relationship of the following formula (2). Ar3+1250×Ceq-450 <FT (2) On the other hand, although there is no particular upper limit to the rolling finish temperature, if the rolling finish temperature is set too high, it becomes necessary to increase the reduction rate per pass, which leads to an increase in defects on the steel sheet surface and an increase in the load on the rolling machine due to rolling under high load. Therefore, from the viewpoint of reducing such defects and the increase in load, the rolling finish temperature is preferably 900°C or less. The rolling finish temperature (FT) to be controlled is the maximum temperature in the width direction.
[0062] (f) Cooling method: Cool the steel plate to room temperature at a cooling rate of 5.0°C / s or less at a position 0.5 mm from the surface. In the present invention, after hot rolling, the steel sheet is cooled to room temperature. By controlling the cooling rate at a position 0.5 mm from the surface of the steel sheet during this cooling as follows, a predetermined microstructure can be generated and the flatness of the steel sheet can be ensured even when the sheet thickness is thin. When the cooling rate exceeds 5.0°C / s, bainite increases from the surface of the steel sheet to a position 0.5 mm from the surface, the deformation of the steel sheet increases, and the maximum value of the gap between the surface of the steel sheet and the long length when a 2 m long length is applied (meaning the average value of the maximum values defined in the examples described later) exceeds 14 mm. Note that air cooling in which the steel sheet is left stationary in the atmosphere is recommended as the cooling method, but a method using a refrigerant with controlled flow rate, pressure, temperature, etc. is also applicable. The cooling rate is determined as the average speed from the hot rolling end temperature to room temperature. Here, if the maximum gap between the surface of the steel sheet and the 2 m long piece after the hot rolling exceeds 14 mm, it becomes difficult to use the steel sheet for the manufacture of the tank as described above unless a separate straightening process is performed. Therefore, in the present invention, a steel sheet with a maximum gap of 14 mm or less is called a steel sheet with excellent flatness.
[0063] A steel plate having the above-mentioned structure (steel plate according to the present invention) can be obtained by manufacturing a steel material having the above-mentioned composition according to the above-mentioned manufacturing conditions. The steel plate according to the present invention thus obtained has excellent strength properties and low-temperature toughness. Here, excellent strength properties mean that YS (upper yield point when there is a yield point, 0.2% proof stress when there is no yield point) is 325 MPa or more and 440 MPa or less. In addition, the International Maritime Organization's IMO Gas Code and ship classification rules stipulate that the yield point of steel plates must be 440 MPa or less to minimize the risk of ammonia stress corrosion cracking. Therefore, if the YS is 440 MPa or less, it can be said that the steel has excellent resistance to ammonia stress corrosion cracking.
[0064] In addition, the higher the TS of the steel sheet, the better, but a steel sheet with a TS of more than 620 MPa is likely to crack during processing or welding. Alternatively, a large amount of alloy will be added, which is likely to increase the cost. Furthermore, since it is difficult to achieve both the aim of controlling the YS to 440 MPa or less in order to ensure excellent ammonia stress corrosion cracking resistance and the improvement of TS, it is desirable to set the TS of the steel sheet to less than 620 MPa. The TS of the steel sheet obtained in the present invention is less than 620 MPa.
[0065] In the steel sheet and the manufacturing method thereof according to the present invention, any items not described in this specification can use the same standards and conventional methods as those for known steel sheets. EXAMPLES
[0066] Molten steel having the composition shown in Table 1 (the balance being Fe and unavoidable impurities) was produced as steel materials (slabs). These steel materials (slabs) were subjected to hot rolling and cooling under the conditions shown in Table 2. In Table 2, A was defined as the left side of the above formula (2): Ar3+1250×Ceq-450.
[0067] The microstructure volume fraction and ferrite grain size distribution at the position 0.5 mm from the surface and at the position 1 / 4 of the plate thickness of the steel plate thus obtained were measured, and the tensile properties and toughness at low temperatures were evaluated.
[0068] [Measurement of microstructure volume fraction and ferrite grain size distribution] Observation samples were taken from each steel plate so that the center was 0.5 mm from the surface and 1 / 4 of the plate thickness. The surfaces of the samples were mirror-polished and further etched with nital, and then photographed using a scanning electron microscope (SEM). The photographed area was 1 mm x 3 mm for the sample taken 0.5 mm from the surface of the steel plate, and 4 mm x 3 mm for the sample taken 1 / 4 of the plate thickness. The area fraction of the microstructure was determined by analyzing the captured image using an image analyzer. Since the steel sheet of the present invention has a small anisotropy of the microstructure and the two-dimensional information obtained by the analysis has universality, the area fraction of the microstructure was considered to be equivalent to the volume fraction, and the area fraction was taken as the volume fraction in the present invention.
[0069] The microstructures were classified as follows when determining the volume fraction of the microstructure: ferrite was defined as a structure that did not contain isotropically grown carbides and was surrounded by white lines, and pearlite was defined as a structure that was lumpy or flat and had a striped pattern of dark ferrite and white carbides. Bainite was defined as a structure that had a long and thin grown lath-shaped ferrite structure and contained carbides with a circle equivalent diameter of 0.05 μm or more, and martensite was defined as a structure that had a long and thin grown lath-shaped ferrite structure and contained no carbides with a circle equivalent diameter of 0.05 μm or more. Note that the carbides were considered to look like white dots. Furthermore, austenite is defined as a structure that exists between bainite and martensite structures and is not defined as carbides.
[0070] The circular equivalent diameter of ferrite was calculated by counting the number of pixels within the area surrounded by grain boundaries as a single crystal in the image file taken with the microscope, and the circular equivalent diameter was calculated by converting the number of pixels into an actual length. Here, as mentioned above, noise due to insufficient resolution of the image to be analyzed or lens focus deviation during shooting may be judged as one crystal grain, and calculations may be made to make it appear that a huge number of minute ferrites exist. Therefore, in obtaining the particle size distribution of the present invention, the particle size distribution was obtained by randomly selecting 4,000 or more ferrites with a size that can be visually judged as a crystal, that is, a circle equivalent diameter of 2 μm or more.
[0071] [Strength characteristics] For each steel plate, a tensile test piece conforming to JIS Z2241 (2022) was taken in the direction perpendicular to the rolling direction, i.e., in the plate width direction, and a tensile test was performed in the manner described in JIS Z 2241 (2022) to measure YS and TS. In this embodiment, steel plates with YS of 325 MPa to 440 MPa were evaluated as having excellent ammonia stress corrosion cracking resistance, and steel plates with TS of 440 MPa to 610 MPa were evaluated as having excellent tensile strength. The yield strength YS is closely related to ammonia stress corrosion cracking resistance, and since it is necessary to minimize the risk of ammonia stress corrosion cracking as a structural member of a liquefied gas bulk carrier, the IMO gas code and ship classification rules stipulate that the yield point of the steel plate is 440 MPa or less. For this reason, steel plates with YS of 325 MPa to 440 MPa were determined to have excellent ammonia stress corrosion cracking resistance.
[0072] [Toughness] Test pieces according to JIS Z2242 (2023) were taken from the area cut 0.5 mm deep from the surface side of each steel plate so that the plate width direction coincided with the longitudinal direction of the test piece. Then, a Charpy impact test was performed as described in JIS Z2242 (2023) to measure the brittle-ductile fracture transition temperature vTrs. In the present invention, a steel plate with a vTrs of -60°C or less was evaluated as having excellent low-temperature toughness.
[0073] [Flatness] When a 2 m long piece (for example, a long piece conforming to JIS B 7516) was placed against the surface of each steel plate along the rolling direction, the gap between the steel plate surface and the long piece was measured with a feeler gauge, and the maximum value of the gap was determined. The measurement was performed at three locations, namely, the center in the width direction of the steel plate and within 50 mm from both ends, as shown in Fig. 1, and the maximum gap value in each of the three measurements was calculated, and the average value of the three maximum values was evaluated. In the present invention, for the reasons described above, a steel plate having an average value of the three maximum values of 14 mm or less was evaluated as having excellent flatness.
[0074] The evaluation results thus obtained are shown in Table 3.
[0075] [Table 1]
[0076] [Table 2]
[0077] [Table 3]
[0078] As can be seen from Tables 1 to 3, all of the examples of the invention have a yield strength YS of 325 MPa to 440 MPa, a tensile strength TS of 440 MPa to 610 MPa, and a brittle-ductile fracture transition temperature vTrs of -60°C or lower, and are excellent in toughness and ammonia stress corrosion cracking resistance at low temperatures. In addition, all of the examples of the invention are steel plates with excellent flatness.
[0079] On the other hand, in the steel plates Nos. 2, 3, 4, 5, 29, 34, 37, and 38, which correspond to the comparative examples, at least one of the volume fraction of the microstructure and the grain size distribution of ferrite is outside the range of the present invention, and therefore at least one of the yield strength YS, tensile strength TS, and toughness at low temperatures is inferior to the invention examples.
[0080] Furthermore, steel plate No. 6, which corresponds to the comparative example, has a high volume fraction of bainite structure at a position 0.5 mm from the steel plate surface, which reduces toughness at low temperatures, and also has poor flatness due to the high cooling rate.
[0081] Furthermore, in steel plates Nos. 20 to 36, the contents of various elements are outside the ranges of the present invention, and therefore at least one of the yield strength YS, tensile strength TS, and low temperature toughness is inferior to the invention examples.
[0082] Steel plate No. 40 has a difference between the maximum and minimum temperatures in the width direction of the steel plate outside the range of the present invention, and therefore has poor flatness.
Claims
1. In mass percent, C: 0.06% or more and 0.13% or less, Si: 0.10% or more and 0.30% or less, Mn: 0.50% or more and 2.00% or less, P: 0.030% or less, S: 0.0030% or less, Al: 0.010% or more and 0.060% or less, Nb: 0.005% or more and 0.030% or less, Ti: 0.004% or more and 0.030% or less, Ca: 0.0005% or more and 0.0030% or less, N: 0.0010% or more and 0.0070% or less; O: 0.0040% or less; The carbon equivalent (Ceq) represented by the following formula (1) is 0.31 or more and 0.40 or less, with the balance being Fe and unavoidable impurities, The volume fraction of bainite at a position 0.5 mm from the surface of the steel plate is 20% or less, Furthermore, at the position of 1 / 4 of the plate thickness, The volume fraction of ferrite is 50% or more and 90% or less, And the total number of ferrite particles having a circle equivalent diameter of 2 μm or more. The number ratio of ferrite particles having a circle equivalent diameter of less than 10 μm is 80% or more and 95% or less, The percentage of ferrite particles having a circle equivalent diameter of 10 to 20 μm is 4% or more and 20% or less, The percentage of ferrite particles having a circle equivalent diameter exceeding 20 μm is 1% or less. steel plate. Ceq=C+Mn / 6+(Cu+Ni) / 15+(V+Mo+Cr) / 5 (1) Here, the element symbols in the above formula (1) represent the content (mass%) of each element in the steel, and when no element is contained, the value is taken as 0.
2. In addition to the above-mentioned component composition, in mass%, Cu: 2.00% or less, Ni: 2.00% or less, Cr: 1.00% or less, Mo: 1.00% or less, V: 1.00% or less, W: 1.00% or less; Co: 1.00% or less The steel sheet according to claim 1, comprising one or more selected from the following:
3. The steel sheet according to claim 1 or 2, wherein when a 2 m long piece is applied to a surface of the steel sheet along the rolling direction, the maximum value of the gap between the surface of the steel sheet and the long piece is 14 mm or less.
4. In mass percent, C: 0.06% or more and 0.13% or less, Si: 0.10% or more and 0.30% or less, Mn: 0.50% or more and 2.00% or less, P: 0.030% or less, S: 0.0030% or less, Al: 0.010% or more and 0.060% or less, Nb: 0.005% or more and 0.030% or less, Ti: 0.004% or more and 0.030% or less, Ca: 0.0005% or more and 0.0030% or less, N: 0.0010% or more and 0.0070% or less; O: 0.0040% or less; A steel material having a composition in which the carbon equivalent (Ceq) represented by the following formula (1) is 0.31 or more and 0.40 or less, with the balance being Fe and unavoidable impurities, When hot rolling, After heating to a temperature of 950°C or more and 1250°C or less, The hot rolling start temperature is Ar 3 Transformation point +150℃ or higher, The cumulative rolling reduction in the non-recrystallization temperature region is 25% or more and 75% or less, The difference between the maximum temperature and the minimum temperature in the width direction of the steel sheet during rolling in the non-recrystallization temperature region is set to 50° C. or less, Hot rolling is performed so that the hot rolling finish temperature (FT) satisfies the relationship of the following formula (2), After the hot rolling is completed, the steel sheet is cooled to room temperature at a cooling rate of 5.0° C. / s or less at a position 0.5 mm from the surface. Manufacturing method of steel plate. Ceq=C+Mn / 6+(Cu+Ni) / 15+(V+Mo+Cr) / 5 (1) Here, the element symbols in formula (1) represent the content (mass%) of each element in the steel, and when no element is contained, the value is taken as 0. Ar 3 +1250×Ceq-450<FT (2) Here, FT is the hot rolling finish temperature (°C), Ar 3 is Ar during the cooling process 3 Represents the transformation point temperature (℃).
5. In addition to the above-mentioned component composition, in mass%, Cu: 2.00% or less, Ni: 2.00% or less, Cr: 1.00% or less, Mo: 1.00% or less, V: 1.00% or less, W: 1.00% or less; Co: 1.00% or less The method for producing a steel sheet according to claim 4, further comprising the step of:
Citation Information
Patent Citations
Production of steel for welding structure
JP1996073934A
High strength thick steel plate for structural purpose having excellent brittle crack arrest property, and method for producing the same
JP2008214653A
Steel plate excellent brittle crack propagation stopping characteristics and manufacturing method therefor
JP2018076573A
Low-yield-ratio thick steel plate
JP2019214751A
Steel for pressure vessels with excellent resistance to hydrogen-induced cracking (HIC) and its manufacturing method
JP2019504210A